2006
DOI: 10.1096/fj.04-3300com
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that aquaporin 1 is a major pathway for CO2transport across the human erythrocyte membrane

Abstract: We report here the application of a previously described method to directly determine the CO2 permeability (P(CO2)) of the cell membranes of normal human red blood cells (RBCs) vs. those deficient in aquaporin 1 (AQP1), as well as AQP1-expressing Xenopus laevis oocytes. This method measures the exchange of (18)O between CO2, HCO3(-), and H2O in cell suspensions. In addition, we measure the alkaline surface pH (pH(S)) transients caused by the dominant effect of entry of CO2 vs. HCO3(-) into oocytes exposed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
240
7
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(266 citation statements)
references
References 32 publications
18
240
7
1
Order By: Relevance
“…As described in ref. 6, exposing an AQP1-expressing oocyte to a solution containing 5% CO 2 /33 mM HCO 3 Ϫ at a constant pH of 7.50 causes a transient rise in pH S , followed by an exponential decay (Fig. 1C Left, green record).…”
Section: Results Phs Transientsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in ref. 6, exposing an AQP1-expressing oocyte to a solution containing 5% CO 2 /33 mM HCO 3 Ϫ at a constant pH of 7.50 causes a transient rise in pH S , followed by an exponential decay (Fig. 1C Left, green record).…”
Section: Results Phs Transientsmentioning
confidence: 99%
“…We used microelectrodes to measure pH S (6,50). Briefly, the pH electrode had a tip diameter of 15 m, was filled at its tip with H ϩ ionophore mixture B (Catalog no.…”
Section: Measurement Of Surface Phmentioning
confidence: 99%
“…To monitor pHS, the tips (diameter ϭ 15 m) of microelectrodes were filled with H ϩ ionophore mixture B (catalog no. 95293; Fluka Chemical, Ronkonkoma, NY), and the electrodes were connected to a model FD223 electrometer (World Precision Instruments, Sarasota, FL) (16,42,43). The extracellular reference electrode was a glass micropipette filled with 3 M KCl, connected to a model 750 electrometer (World Precision Instruments), via a calomel half-cell.…”
Section: Physiological Measurementsmentioning
confidence: 99%
“…Figure 2 shows representative traces. An alkalinization (rise in pH S ) is indicative of CO 2 influx (16,41,42,44). Conversely, an acidification (decrease in pH S ) indicates an influx of NH 3 .…”
Section: Co 2 and Nh 3 Permeabilitymentioning
confidence: 99%
“…In particular, the role of AQP1 as a CO 2 channel has been a matter of lively debate ever since it has been reported that AQP1 increases the CO 2 permeability of Xenopus oocytes membranes (Nakhoul et al 1998). By now, aquaporins have been reported to increase the CO 2 permeability of membranes of oocytes (Cooper and Boron 1998;Nakhoul et al 1998), liposomes (Prasad et al 1998), and red blood cells (Blank and Ehmke 2003; Endeward et al 2006). Other studies did not report any impact of AQP1 on membrane CO 2 permeability (Yang et al 2000).…”
Section: Are Aquaporins Permeated By Gas?mentioning
confidence: 99%